Program Literasi Keuangan Syariah Untuk Siswa Sebagai Upaya Membangun Generasi Ekonomi Umat - Mustamin, Sitti Walida; Nurpaidah, Nurpaidah; Suci Tri Wardani; Khairatil Mar’ah; Suharni, Suharni; Nilawati, Nilawati; Sri Indah Lestari; Fadlia Indasari; Warda Toatubun; Nurazizah Rusyda; Ratnadila Anggraini (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The financial literacy program is a strategic step in building a generation of the ummah that is integral, productive, and based on Islamic values by developing a sharia financial literacy program for students. The lack of public interest in Islamic economics is one of the reasons why there is a need to enhance Islamic economic literacy. With the implementation of community service conducted by Muhammadiyah University in the Al Islam and Kemuhammadiyahan course at Unismuh Makassar Junior High School, the aim is to provide education, inspire, and guide in enhancing the community's understanding of sharia economics. This research shows that students who participate in this program will have a better understanding of the basic concepts of sharia finance and will be more capable of applying them to their personal financial management. This program not only makes students more knowledgeable about finance but also makes them aware that they can help build a sustainable community economy.